Pengaruh Value Congruity dan Psychological Ownership terhadap Loyalty: Peran Consumer Engagement Sebagai Variabel Mediasi - Khafilia Adi Tama Sari (Jurnal Ilmu Manajemen, 2022)
There are so many researches talks about marketing, especially about loyalty. But only a view of them raises the topic of loyalty in the music industry so that many things can be disseminated in the music industry, including musicians. Flexibility in listening to music through digital music platforms is among many ways to spread loyalty among listeners towards musicians. One of the musicians who get the loyalty of their music listeners in a large number and relatively short time is The Panturas. This study discusses things that might affect the occurrence of those phenomena using quantitative methods, especially the causal relationship of value congruity and psychological ownership to the loyalty of The Panturas' listeners with consumer engagement on their official Twitter account as a mediating variable. The sample collection technique used is non-probability sampling with a total sample of 200 respondents from The Panturas' music listeners. All the respondents were filtered through screening questions where they must meet the criteria as listeners of The Panturas's music who follow and have interacted in the form of comments, quote tweets, direct messages, or mentions on The Panturas' official Twitter account. This study uses data analysis techniques named path analysis which contains hypothesis testing, model analysis, and Sobel test to determine the role of mediating variable. The results of this study indicate that all hypotheses are accepted. Still, the mediating variable studied, consumer engagement, doesn't play its role as a mediator of the relationship between value congruity and psychological ownership with loyalty.